Kazakhstan : Overview of Climate Change Activities - World Bank (Washington, DC, 2014)
This overview of climate change activities in Kazakhstan is part of a series of country notes for five Central Asian countries that summarize climate portfolio of the major development partners in a number of climate-sensitive sectors, namely energy, agriculture, forestry, and natural resources, water, health, and transport. Recognizing the nature and significance of climate change contribution to an increase in disaster risk, the note also looks into the development partners' approaches and measures in this area. The note further provides a brief overview of Kazakhstan's climate context in terms of observed impacts and historical trends as well as climate projections specific to sectors that are considered to be essential to the country's economic development. Finally, the note assesses national policy and institutional context related to climate change and suggests potential ways forward that can help Kazakhstan mainstream low-carbon, climate-resilient development.